sj-docx-1-isp-10.1177_00207640221141784 – Supplemental material for Social anxiety and depression symptoms in Chinese left-behind children after the lifting of COVID-19 lockdown: A network analysis - Kuiliang Li; Lei Ren; Lei Zhang; Chang Liu; Mengxue Zhao; Xiaoqing Zhan; Ling Li; Xi Luo; Zhengzhi Feng (SAGE Journals, 2022)
Supplemental material, sj-docx-1-isp-10.1177_00207640221141784 for Social anxiety and depression symptoms in Chinese left-behind children after the lifting of COVID-19 lockdown: A network analysis by Kuiliang Li, Lei Ren, Lei Zhang, Chang Liu, Mengxue Zhao, Xiaoqing Zhan, Ling Li, Xi Luo and Zhengzhi Feng in International Journal of Social Psychiatry
Keywords: Psychology not elsewhere classified; Psychiatry (incl. Psychotherapy)